HDI XMAS July 15, 2019. Geraldine Legge photos. - Barrett, Terra (1941)
A black and white photo of the Heart's Delight SUF Band holding their instruments. Unknown person, unknown, Raymond Legge, unknown, Joseph Crocker, unknown, Arthur Crocker, unknown, unknown, unknown, (seated) Bill Welsh, Theophileus Chislett, unknown, unknown, and Ambrose Perry.